Association between the estimated glucose disposal rate and the occurrence of major cardiovascular events and stroke - Yue-Yang Zhang; Qin Wan (Diabetology & Metabolic Syndrome)
Abstract Background The Estimated Glucose Disposal Rate (eGDR) recognised as a reliable biomarker for assessing insulin resistance. Accordingly, this study aims to investigate the potential association between eGDR and the occurrence of major adverse cardiovascular events (MACE) and stroke within a cohort of the Chinese population. Methods The China Cardiometabolic Disease and Cancer Cohort Study is a large-scale, nationwide, multicenter prospective cohort study initiated in 2010. The study collected baseline data from 10,008 participants, with a subsequent 10-year follow-up period. Following the relevant inclusion and exclusion criteria, a total of 8,723 participants were included in the final analysis. Participants were stratified into four groups based on the quartiles of their eGDR levels. To better evaluate the association between eGDR and the risks of MACE and stroke, the study employed Cox proportional hazards models, restricted cubic splines (RCS), receiver operating characteristic curve(ROC), and subgroup analyses to ensure the robustness of the findings. Results A total of 438 MACE events and 445 stroke events were documented. Cox regression and RCS analyses demonstrated a negative association between eGDR and the risk of both MACE and stroke in fully adjusted models. Specifically, each one standard deviation increase in eGDR was associated with a 2% reduction in the risk of MACE and stroke. Moreover, compared with participants in the Q1 group, those in the Q4 group exhibited a significantly lower risk of primary outcomes. The RCS analysis identifies an optimal eGDR threshold of 9.92. Additionally, the ROC demonstrates that incorporating eGDR significantly enhances the diagnostic efficacy compared to the basic model and other positive controls. Conclusions Elevated eGDR levels are associated with a lower risk of MACE and stroke among non-diabetic individuals in China.